Landasan Pendidikan Islam - Idam Mustofa (Asosiasi Dosen Tarbiyah STAI Darussalam Nganjuk, 2021)
The national education system has established educational standards adopted in Islamic education providers in Indonesia as a whole. This preference of course leaves the question, the extent to which the foundation of education has been met by national education standards. This descriptive-analytical study outlines the foundation of Islamic education covered by national standards of education. From this study it can be identified that the foundation of Islamic education is relevant to the educational standards set by the national education system. The national education system has contained humanitarian values with various conditions, challenges and changing times that very quickly undermine the values of literature itself. The national education system has demonstrated efforts to transform people with knowledge with attitudes and behaviors that fit the framework of Islamic values. Because the purpose of education creates human resources with Islamic personality, in the sense of how to think based on Islamic values and spirit in accordance with the spirit and breath of Islam